2016
DOI: 10.5935/1415-2762.20160021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Diagnostic Accuracy of Undergraduate Students and Nurses in Residency Programs

Abstract: Objetivos: comparar o grau de acurácia diagnóstica entre estudantes do último ano de graduação em ENFERMAGEM e de enfermeiros residentes, e estimar a associação entre o grau de acurácia diagnóstica e o grau de contato com processo de enfermagem, diagnóstico de enfermagem, raciocínio clínico e o grau de habilidade em estabelecer diagnósticos de enfermagem. Método: trata-se de estudo descritivoexploratório transversal. Participaram 65 sujeitos, dos quais: 27 graduandos do último ano de Enfermagem, 19 enfermeiros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
1
7
0
6
Order By: Relevance
“…A similar result was found in a study that evaluated the Nursing diagnoses of undergraduates and Nursing residents where the students enrolled significantly more number of ND than the residents. 10 It was also verified that, the greater the number of participation in Clinical Visit, the smaller number of diagnoses are raised and less diagnoses of low or zero accuracy are listed.…”
Section: It Was Shown Inmentioning
confidence: 89%
See 2 more Smart Citations
“…A similar result was found in a study that evaluated the Nursing diagnoses of undergraduates and Nursing residents where the students enrolled significantly more number of ND than the residents. 10 It was also verified that, the greater the number of participation in Clinical Visit, the smaller number of diagnoses are raised and less diagnoses of low or zero accuracy are listed.…”
Section: It Was Shown Inmentioning
confidence: 89%
“…2,10-11-12 A study conducted with undergraduate students and Nursing residents of the first and second years of Nursing residency at a public university in São Paulo showed that Nursing residents of the 2nd year registered a lower number of ND with low accuracy due to the longer inservice training. 10 A study was conducted by researchers with the objective of evaluating the accuracy of the diagnosis of acute pain in hospitalized children in the period before and after the implementation of an inservice training program. The Nursing diagnosis investigated showed moderate / high accuracy during the study period, but four months later the accuracy became prevalent low / null.…”
Section: It Was Shown Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Benner (2001) emphasized that educational level and years of professional experience may influence nurses’ ability to make clinical judgments. In fact, as evidenced by other researchers, second‐year resident nurses identified a lower number of diagnoses with low accuracy in comparison with first‐year resident nurses and undergraduate nursing students (Oliveira & Silva, 2016).…”
mentioning
confidence: 72%
“…These skills may be learned and developed, so that the ability to make judgments with accuracy may be enhanced by means of teaching and practice (Carvalho et al, 2017; Oliveira & Silva, 2016). Benner (2001) emphasized that educational level and years of professional experience may influence nurses’ ability to make clinical judgments.…”
mentioning
confidence: 99%